Menelusuri Kasih Ilahi dalam 1 Yohanes 4:7-12 : Dampak dan Penerapannya dalam Kehidupan Sehari-hari - Robin Stefanus Zalukhu; Malik Bambangan (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This research discusses the concept of divine love as conveyed in 1 John 4:7-12, as well as its impact and application in daily life. These verses outline love as the essence of God's nature and as a call for each individual to reflect it in social interactions. The emphasis on love that comes from God reveals a deep connection between the knowledge of God and the ability to love others. Through an expository approach, this study analyzes the structure of the text to identify the theological and practical implications of God's emanating love, including the demand for everyone to emulate divine love in concrete action. In this study, it lies in the elaboration that divine love not only plays a role as a transcendent attribute, but also as a force that shapes and inspires human relationships. . This understanding introduces a new perspective in the development of more authentic and empathic relationships in contemporary social contexts. By examining the application of this doctrine, this article leads to an understanding that divine love is not just a theological principle, but a call to concrete action in everyday life.